1989
DOI: 10.1111/j.1439-0442.1989.tb00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Analysis of Canine Transmissible Sarcoma Cells

Abstract: Summary The chromosomal banding patterns of canine transmissible sarcoma (CTS) cells were analyzed and compared to those of normal canine cells with four banding techniques. In addition, N‐myc and N‐ras oncogenes on the chromosomes of the CTS cells were investigated by the in situ hybridization method. The modal chromosome number of the CTS cells was 58:17 metacentrics and 41 acrocentrics. Based on their G‐ and Q‐banding patterns most of the chromosomes of the CTS cells were present in normal cells except for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 24 publications
1
17
0
Order By: Relevance
“…Gene names and descriptions are taken from the Human Gene Nomenclature Database (http://www.genenames.org/) 2006). It is interesting to note that cytogenetic analysis of CTVT in the present study revealed that all tumors had the sex chromosome complement XO, regardless of the gender of the affected dog host, which is consistent with some earlier studies (for example, Fujinaga et al 1989). All five cases also showed loss of the pseudoautosomal region of the remaining X chromosome, extending~6 Mb from CFA Xptel (Young et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Gene names and descriptions are taken from the Human Gene Nomenclature Database (http://www.genenames.org/) 2006). It is interesting to note that cytogenetic analysis of CTVT in the present study revealed that all tumors had the sex chromosome complement XO, regardless of the gender of the affected dog host, which is consistent with some earlier studies (for example, Fujinaga et al 1989). All five cases also showed loss of the pseudoautosomal region of the remaining X chromosome, extending~6 Mb from CFA Xptel (Young et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The normal karyotype of the domestic dog (Canis familiaris, CFA, 2n=78) comprises 38 pairs of acrocentric autosomes plus submetacentric sex chromosomes X and Y. In contrast, CTVT cells reportedly present with a modal number of 57-59 chromosomes, of which 16-18 are considered metacentric and the remainder acrocentric, indicative of a tremendous degree of structural reorganization (Makino 1963;Murray et al 1969;Adams et al 1981;Vermooten 1987;Fujinaga et al 1989). This decrease in total chromosome number has been widely attributed to the formation of bi-armed derivative chromosomes through multiple centric fusion events between acrocentric chromosomes.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…Whereas the constitutive chromosome number of dogs is 78, the karyotypes of CTVT tumors from Japan, Uganda, Jamaica, France, the United States, Nigeria and Russia all confirmed a chromosome number of 57-59 (Sofuni and Makino, 1963;Weber et al, 1965;Barski and Cornefert-Jensen, 1966;Kakpakova et al, 1968;Thorburn et al, 1968;Murray et al, 1969;Wright et al, 1970;Oshimura et al, 1973;Idowu, 1977;Richardson et al, 1987;Fujinaga et al, 1989). The CTVT karyotype included 15-17 metacentric or submetacentric chromosomes, in contrast to 2 in the normal dog karyotype.…”
Section: Ctvtmentioning
confidence: 99%